2021
DOI: 10.1027/1864-9335/a000441
|View full text |Cite
|
Sign up to set email alerts
|

The Voice Gives It Away

Abstract: Abstract. Two experiments examined the impact of voice pitch on gender stereotyping. Participants listened to a text read by a female (Study 1; N = 171) or male (Study 2, N = 151) speaker, whose voice pitch was manipulated to be high or low. They rated the speaker on positive and negative facets of masculinity and femininity, competence, and likability. They also indicated their own gendered self-concept. High pitch was associated with the ascription of more feminine traits and greater likability. The high-pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Stronsick and colleagues (2018) reported that excerpts played in a traditionally feminine instrument timbre were rated as less feminine when presented in a low pitch than a high pitch (and vice versa). They interpreted their results as paralleling research in gender identification of human voices -the same gender-pitch links are observed (Krahé & Papakonstantinou, 2020;Krahé et al, 2021;Pernet & Belin, 2012). By around 6 years, children associate higher pitched voices with femininity and lower pitched voices with masculinity (Cartei et al, 2019;Nagels et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…Stronsick and colleagues (2018) reported that excerpts played in a traditionally feminine instrument timbre were rated as less feminine when presented in a low pitch than a high pitch (and vice versa). They interpreted their results as paralleling research in gender identification of human voices -the same gender-pitch links are observed (Krahé & Papakonstantinou, 2020;Krahé et al, 2021;Pernet & Belin, 2012). By around 6 years, children associate higher pitched voices with femininity and lower pitched voices with masculinity (Cartei et al, 2019;Nagels et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…An alternative possible explanation is similar to the logic mentioned before that a male speaker with high experience can be regarded as violating gender stereotypes. A male speaker with higher pitched voice may also be perceived as violating gender stereotypes expectations (Krahé et al, 2021), and this may lead participants to be less favourable to the target speakers because people who deviate from gender stereotypic expectations can encounter backlash (Moss‐Racusin et al, 2010; Moss‐Racusin, 2014; Rudman & Phelan, 2008), and in turn suppressed the total effect on behavioural intentions. These possible suppressor effects were not a focus of the current research but awaits future inspection.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing that the effect of voice pitch on social perception (e.g., stereotyping) varies by speaker's sex. For instance, Krahé et al (2021) found that the higher-(vs. lower-)pitched female speaker was rated as possessing more femininity but not masculinity, while the lower-(vs. higher-)pitched male speaker was rated higher on masculinity and lower on femininity. Furthermore, this research indicated different results of moderation by sex in listeners' stereotyping such that warmth ratings were higher for both higher-(vs. lower-)pitched female and male speakers, whereas competence ratings were higher for the lower-(vs. higher-)pitched female speaker only.…”
Section: Study 1: the Influence Of Voice Pitch On Mind Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we considered studies looking at the interplay between voice‐based identity, masculinity, and gender stereotyping. Studies have demonstrated that vocal features are cues to gender stereotyping (Ko et al., 2006; Krahé et al., 2021; Krahé & Papakonstantinou, 2020) and that, in hiring situations, sounding masculine increased perceived competence, and this is more important than the candidate's actual gender (Ko et al., 2009). Together with the perception of masculine/feminine‐sounding speakers comes the recent work concerning the stigmatization of gay/lesbian‐sounding speakers.…”
Section: Introductionmentioning
confidence: 99%